Genome evolution of blind subterranean mole rats: Adaptive peripatric versus sympatric speciation - Li, Kexin; Zhang, Shangzhe; Song, Xiaoying; Weyrich, Alexandra; Wang, Yinjia; Liu, Xi; Wan, Na; Liu, Jianquan; Lövy, Matěj; Cui, Haihong; Frenkel, Vladimir; Titievsky, Avi; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Speciation mechanisms remain controversial. Two speciation models occur in Israeli subterranean mole rats, genus Spalax: a regional speciation cline southward of four peripatric climatic chromosomal species and a local, geologic-edaphic, genic, and sympatric speciation. Here we highlight their genome evolution. The five species were separated into five genetic clusters by single nucleotide polymorphisms, copy number variations (CNVs), repeatome, and methylome in sympatry. The regional interspecific divergence correspond to Pleistocene climatic cycles. Climate warmings caused chromosomal speciation. Triple effective population size, Ne , declines match glacial cold cycles. Adaptive genes evolved under positive selection to underground stresses and to divergent climates, involving interspecies reproductive isolation. Genomic islands evolved mainly due to adaptive evolution involving ancient polymorphisms. Repeatome, including both CNV and LINE1 repetitive elements, separated the five species. Methylation in sympatry identified geologically chalk-basalt species that differentially affect thermoregulation, hypoxia, DNA repair, P53, and other pathways. Genome adaptive evolution highlights climatic and geologic-edaphic stress evolution and the two speciation models, peripatric and sympatric.
Keywords: mužské pohlaví; tok genů; Male; reprodukční izolace; Genetic Variation; molekulární evoluce; Israel; variabilita počtu kopií segmentů DNA; speciation models; repeatome; Polymorphism, Single Nucleotide; Adaptation, Biological; Genetics, Population; Biological Evolution; jednonukleotidový polymorfismus; epigeneze genetická; vazebná nerovnováha; Gene Flow; Epigenesis, Genetic; Genome; genomic sequencing; DNA Copy Number Variations; genom; genetická variace; Animals; Spalax; biologická adaptace; zvířata; methylation; populační genetika; sympatrie; Sympatry; biologická evoluce; Izrael; Linkage Disequilibrium; Reproductive Isolation; Evolution, Molecular; subterranean rodents